ANALISIS PENGARUH STRUKTUR MODAL (CAR) DANDANA PIHAK KETIGA (FDR) TERHADAP PROFITABILITAS (ROA) DENGAN KREDIT BERMASALAH (NPF) SEBAGAI VARIBEL INTERVENING PADA PERBANKAN UMUM SYARIAH DI INDONESIA - Fitria Marisya (Jurnal Ilmu Akuntansi, 2019)
This research focuses on the analysis of the influence of capital structure (Capital Adequacy Ratio/ CAR) and third-party Funds (Financing to Deposit Ratio/ FDR) towards Profitability (Return on Asset/ ROA) with Troubled Financing (Non Performing Financing/ NPF), as the Intervening Variables in the Public Sharia Banking In Indonesia. The data was obtained from the Indonesian Capital Market Directory (ICMD)and analyzed using Path Analysis with the help of AMOS programs22.The test results show some impact as follows: 1. The CAR has a positive and significant to FDR. 2. The NPF is not positive and significant to FDR. 3. The CAR is positive and significant to ROA. 4. The NPF is negative and significant to ROA. 5.The FDR is positive and significant to ROA. 6.The FDR is a significant intervening intervening variable between CAR and ROA in the form of partial mediation. 7.The FDRisasignificantandinfluential variable intervening between the NPF and ROA in the form of partial mediation. This research isexpected to be beneficial to investors, among others, and this research can be used as a consideration in making investment decisions. Also, the researchers can use this as a reference for any research related to capital structure (CAR), third-party Funds (FDR), profitability (ROA), and was the troubled Financing(NPF).